STRENGTH AND DIMENSION ACCURACY IN FUSED DEPOSITION MODELING : A COMPARATIVE STUDY ON PARTS MAKING USING ABS AND PLA POLYMERS - Tanoto, Yopi Yusuf; Anggono, Juliana; Budiman, Wesley; Philbert, Kresna Vincent (Rekayasa Mesin, 2020)
Rapid prototyping is a group of techniques used to quickly scale physical parts or assemblies using three-dimensional computer-aided design (CAD) data. The process of 3D printing constructs three-dimensional objects from CAD models, usually by adding layers by a layer of material in a row. Therefore it is also called making addictive manufacturing. Along with the development of rapid prototyping, there are many choices of materials on the market to make parts of 3D printing. The material can be in the solid filament, liquid resin, or powder. Solid filament FDM technology material is the most commonly used by industry ? these materials such as ABS, PLA, PETG, HIPS, and others. In 3D printing products, several variables can be observed to produces specific responses desirable. Some of the responses are the efficiency of materials, dimensional accuracy of mechanical, and others. This research was conducted to compare ABS and PLA materials in the fused deposition modeling process. The strength and dimensional accuracy are the response that used in this study. The study reports that ABS has more significant tensile strength than PLA. The tensile strength of ABS is 7.66 MPa and 1.79 for PLA. PLA found has a more accurate dimension compare to ABS. Both on length and thickness, deviation of PLA lower than ABS. On a length, deviation of PLA was 0.06 mm and 0.86 for ABS. On thickness, deviation of PLA was 0.04 and 0.05 for ABS.